Qeirat Values and Victim Blaming in Iran: The Mediating Effect of Culture-Specific Gender Roles - Karimi-Malekabadi, Farzan (Journal of interpersonal violence, 2023)
Sexual assaults are a social problem in Iran; however, psychological factors that predict perceptions of sexual assault remain largely unexamined. Here, we examine the relationship between moral concerns, culture-specific gender roles, and victim blaming in sexual assault scenarios in Iranian culture. Relying on Moral Foundations Theory and recent theoretical developments in moral psychology in the Iranian context, we examined the correlations between five moral foundations (Care, Fairness, Loyalty, Authority, and Purity), a culture-specific set of values called Qeirat (which includes guarding and [over]protectiveness of female kin, romantic partners, broader family, and country), and victim blaming. In a community sample of Iranians (N = 411), we found Qeirat values to be highly correlated with victim blaming, and that this link was mediated by a number of culture-specific proscriptions about women’s roles and dress code (i.e., Haya). In a regression analysis with all moral foundations, Qeirat values, Haya, and religiosity as predictors of victim blaming, only Haya, religiosity, high Authority values, and low Care values were found to predict how strongly Iranian participants blamed victims of sexual assault scenarios.